PENGARUH KEPRIBADIAN DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI BUDAYA ORGANISASI PADA MADRASAH TSANAWIYAH SWASTA KECAMATAN WINONG KABUPATEN PATI - Nur Muhsin, 12.5202.0226; Sutomo, Y (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aimed to examine the influence of personality and motivation on theperformance of teachers in non-government Islamic Junior High School (MTs Swasta)Winong district Pati regency with organizational culture moderated. The specific objectives ofthis study was to explain and to enlarge the previuos study about the influence of personalityand motivation on the performance of teachers with organizational culture moderated.This study used a population of teachers in non-government Islamic Junior HighSchool (MTs Swasta) Winong District Pati Regency totally 102 teachers. Samplingtechniques in this study is sampling jenuh. This method used is regression with absolutedifference moderation. Based on the results of the study can be summarized as follows: personality has asignificant and positive influence on the teacher performance, motivation has a significantand positive influence on the teacher performance, organizational culture has a significantand positive influence on the teacher performance, but organizational culture do not moderatethe influence of personality and motivation on the teacher’s performance.Keywords: personality, motivation, organizational culture, teacher performance.